Evaluation of an endovascular aneurysm model in pigs for chronic experiments - Lara Bender; Thorsten Sichtermann; Jan Minkenberg; Christoph Dorn; Rebecca May; Charlotte S. Weyland; Dimah Hasan; Andrea Stockero; Hani Ridwan; Martin Wiesmann; Omid Nikoubashman; Christiane Franz (Brain Circulation)
BACKGROUND AND AIMS: Cerebral aneurysms are a potentially life-threatening condition for humans. Due to the anatomical variability of different aneurysm types in human patients, animal models are indispensable for endovascular research. The aim of our study was to evaluate an endovascular aneurysm model in chronical experiments using 12 female Aachen minipigs. MATERIALS AND METHODS: For aneurysm creation in external carotid and subclavian arteries, Amplatzer vascular plugs were used as occlusion devices, leaving simple stumps that serve as surrogate aneurysms. If necessary and anatomically possible, additional embolic materials, such as coils and liquid embolic agents were used. RESULTS: We created 42 aneurysms. Aneurysm creation was possible without complications in all cases. There was no spontaneous thrombosis of fabricated aneurysms. Complete perfusion arrest behind the fabricated aneurysm was challenging but achieved in 45% of cases. We were not able to identify significant factors that have an impact on the persisting perfusion of fabricated aneurysms on final imaging, particularly not the presence of side branches in the aneurysm lumen (P = 0.734) or volumes of the fabricated aneurysms (P = 0.620). Albeit not significant, the use of additional occlusive measures (coils, liquid embolic agents) and antithrombotic drugs (ASA, heparin and tirofiban) may be factors for persisting perfusion: Perfusion arrest behind the fabricated aneurysm was twice as high in animals treated with ASA and heparin compared to animals treated with ASA, heparin, and tirofiban (48% vs. 22%; P = 0.149). CONCLUSION: Despite its limitations, including persistent perfusion and impaired predictability for long-term experiments, the endovascular aneurysm model shows potential to replace certain surgical models and offers broad applications in biomedical research and aneurysm therapy.